Peran Koperasi Simpan Pinjam (KSP) Tunggal Jaya Fakfak I Terhadap Pendapatan dan Usaha Anggotanya di Kabupaten Fakfak - Fahri Alsam (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The history of the birth and development of cooperatives in developed (western) and developing countries is indeed very diametric. In the west cooperatives were born as a Movement to fight against market injustice, therefore growing and developing in an atmosphere of market competition. Even with its strength, cooperatives have achieved a bargaining position and an important position in the constellation of economic policies, including in international negotiations. The laws and regulations that govern cooperatives grew later as a demand of the cooperative community in order to protect themselves. The purpose of the research is to find out how the Role of the Tunggal Jaya Fakfak I Savings and Loan Cooperative (KSP) on the income and business of its members. To find out whether the role of the Tunggal Jaya Fakfak I Savings and Loan Cooperative (KSP) on income and business can improve the welfare of its members. This research method uses quantitative and qualitative methods. The results of this study prove the contribution made by the Tunggal Jaya Fakfak I Savings and Loan Cooperative (KSP) to the Community and its members, so it can be said that the Tunggal Jaya Fakfak I Savings and Loan Cooperative (KSP) plays a very important role in improving the welfare of the community in Fakfak Regency especially the people who are its members so that the standard of living is more guaranteed and the welfare of its members is also achieved due to changes in the income of its members. In conclusion, the Tunggal Jaya Fakfak I Savings and Loan Cooperative (KSP) also has a positive impact on the government in helping to overcome the problem of poverty by playing a role in providing savings and loans, to members and the community in Fakfak Regency, so that the community can develop their businesses.